Pendampingan Pada Nasabah di Unit Layanan Modal Mikro (ULAMM) PT PNM Persero Muara Bulian untuk Mengeliminasi Block Mental sebagai “Musuh” Utama Entrepreneur - Sumarni; Rohman William; Hendriyaldi; Nyimas Dian Maisyarah; Musyaiyadah (Studium: Jurnal Pengabdian Kepada Masyarakat, 2022)
The number of business actors is an important indicator that will show whether a country is developed or not. The large number of entrepreneurs in a country will have an impact on the emergence of jobs which will automatically increase the country's economy. Indonesia experienced an increase of 3.1% of the total population. One of the Indonesian governments presenting PT PNM (Persero) is to contribute to the welfare of the community and advance Indonesian MSMEs, then the aim of PT PNM Persero ULaMM Muara Bulian is to form an entrepreneurial mentality, increase business and improve the economy, in line with the community service activities that will be carried out. The purpose of this service activity is to influence and change the mindset of customers who are "afraid" of facing risks in doing business, besides that it aims to eliminate Mental Blocks and provide assistance so that business actors have character and skills like entrepreneurs. This service will be able to answer the problems that occur in people who do not dare to start a career as entrepreneurs because they have a Mental Block within themselves, especially customers at ULaMM Muara Bulian. The implementing method in this service in delivering training material is using the Ice Breaking method and motivation Session, aiming to encourage participants to take part in the training and to motivate participants while attending the training, Presentation Session, in this method is in the form of a lecture by presenting material that has been prepared by the Team to training participants in the form of PPT slides and video shows and Discussion Sessions, in this session conducting questions and answers/discussions, namely the method used to respond to the extent to which participants understand the material presented by the Team.